The ant genus Carebara Westwood (Hymenoptera, Formicidae): synonymisation of Pheidologeton Mayr under Carebara, establishment and revision of the C. polita species group - Fischer, Georg (Pensoft Publishers, 2014)
Abstract. In this paper the genus Pheidologeton Mayr, 1862 is synonymized under Carebara Westwood, 1840 and the Carebara polita group is established and revised. This species group currently includes six species from the Afrotropical region (C. madibai, C. nicotianae, C. perpusilla, C. polita, C. silvestrii, and C. villiersi) and two species from the Neotropical region (C. brevipilosa and C. urichi). The polita group clearly links Carebara and Pheidologeton, and, due to a lack of autapomorphic characters for the latter, a separation of the two genera is no longer justified. As a result Carebara is presented as a monophyletic and better defined genus that can be separated from other genera with more confidence. We present an overview of the distribution and biology of Carebara as well as images from the various genera currently in synonymy under Carebara, and discuss the characters they share. The polymorphism present in Afrotropical and Malagasy Carebara is discussed and one new species from Africa, C. madibai sp. n., is described. The subspecies Carebara perpusilla arnoldiana syn. n., Carebara perpusilla concedens syn. n., and Carebara perpusilla spinosa syn. n. are new synonyms of Carebara perpusilla. Oligomyrmex politus nicotianae is re-elevated to species level and transferred into Carebara, C. nicotianae comb. n., stat. rev.; C. punctata is a new synonym of C. silvestrii comb. n. and C. pygmaea albipes comb. n., syn n., C. pygmaea bugnioni comb. n., syn. n., and C. simularensis syn. n. are new synonyms of C. pygmaea comb. n.. The following names are transferred from Pheidologeton to Carebara as new combinations (with the species epithets adjusted to female endings where necessary): aberrans, affinis, affinis javana, affinis minor, affinis spinosior, affinis sumatrensis, ceylonensis, dentiviris, diversa, diversa draco, diversa ficta, diversa laotina, diversa macgregori, diversa philippina, diversa standfussi, diversa taprobanae, diversa tenuirugosa, diversa williamsi, hammoniae, hostilis, kunensis, latinoda, maccus, mayri, melanocephala, melasolena, nana, nanningensis, obscura, petulens, pullata, pungens, pygmaea, rubra, rugiceps, rugosa, schossnicensis, silena, silvestrii, solitaria, transversalis, trechideros, varia, vespilla, volsellata, yanoi, and zengchengensis. Three new combinations are creating secondary junior homonyms and are here replaced with new names: C. mayri (Santschi, 1928) = C. gustavmayri nom. n., C. rugosa (Karavaiev, 1935) = C. rugoflabella nom. n., and C. silvestrii (Wheeler, 1929b) = C. luzonensis nom. n. Two new combinations are creating secondary junior homonyms among species already in Carebara: C. taprobanae (Forel, 1911a) = C. sinhala nom. n., and C. nana Santschi, 1919 = C. pumilia nom. n.